FAKTOR-FAKTOR YANG MEMPENGARUH KINERJA KEUANGAN USAHA SUVENIR DI KOTA PALEMBANG - Dewi Sri (Catholic University Musi Charitas, 2018)
The growth of Palembang city coloured by many international events causes souvenir firms develop. Informal sector is a kind of firm which helps family economy. From the phenomenon, there came this research is intended to analyze the capacity of finance resource, intangible assets, and financial performance of the souvenir firms. This research only concerns with small and medium souvenir firms in Palembang city. Data were collected by using questionaires, while method to test the hypothesis used descriptive and regression analysis by SPSS24. The results of this research showed that Intangible Asset more influence in financial performance than financial resource. The role of Intangible assets increased five more times the financial performance, while financial resource only influenced half of it.